Analisis Pengendalian Persediaan Bahan Baku Biji Kakao pada Pabrik Delicacao Bali di Kabupaten Tabanan - MUZAYYANAH, MUZAYYANAH; SUAMBA, I KETUT; DEWI, RATNA KOMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Analysis of raw material inventory control  cocoa beans Delicacao Bali factory in  the district Tabanan   Raw material availability is very important for the production process, therefore Delicacao Bali factory should be able to determine the amount of optimal raw material inventory. Reduce the cost of inventory in order to keep the production process running smoothly. In this case the company needs to analyze the inventory management to be able to minimize the total cost incurred in the  inventory. This study aims to (1) analyze raw material inventory control conducted by Delicacao Bali, (2) analyze alternative raw material inventory control to be applied,the Bali Delicacao to improve the efficiency of the inventory costs. The method used in the study included (1) Qualitative descriptive method and (2) Quantitative Method . The results of analysis the inventory cost, methods MRP of company policy shows that inventory control policy Delicacao Bali cocoa beans is not optimal. The comparison total inventory costs incurred by the company in 2013 amounted to Rp 19,998,452.00, when using the technique of LFL company can issue a total inventory cost of Rp 8,600,000.00, and cost savings (efficiency) reached 54.93 %. While the techniques EOQ company can issue a total cost of Rp 4,109,355.18 and cost savings (efficiency) reached 79.45 %. MRP techniques EOQ is an alternative method that can be recommended to the company as an inventory control techniques in the hopes this method can save the cost of raw material.   Keywords : Inventory cost, MRP, Delicacao Bali